Effects of age and language environment on lexical tone processing - Leung, Kai Yan (2019)
Most studies on the relationship between age and language have focused mainly on the young and the older adults who are aged 60 and above. Little is known about the lexical tone processing abilities of the middle age group. Studies in the recent years has also shown a growing tone merging trend in Hong Kong Cantonese. With age and language environment in mind, this study thus sought to find out the extent to which age would influence lexical tone discrimination and production abilities, as well as how language environment would bring out interplaying effects when taken into the picture. 51 native and heritage speakers of Cantonese were separated into the Young, Old, HK and SG groups as between-subject factors. They were presented with Cantonese word stimuli in an ABX discrimination task, and went through a lexical tone production task. Results suggest that age affects the accuracy of perception scores, however it is not predictive of lexical tone production abilities, while language environment revealed varying group differences in T2/5 contour productions. Young HK speakers have also shown a unique and strong tone merging behaviour in their production data which was not present in the other three experimental groups.